The pharmacological treatment of COVID-19. Conference of Peruvian American Medical Socity (PAMS) - Gonzales-Zamora, Jose Armando (2021)
The pharmacological treatment of COVID-19 has changed a lot during the pandemic. Hydroxychloroquine is not used anymore due to the lack of clinical efficacy. Ivermectin, a medication applied widely in Peru, is not recommended because the scientific evidence to support its use is insufficient. To date, the treatment of hospitalized patients is based in Remdesivir and corticosteroids, and it is only symptomatic without empiric antibiotics in the ambulatory setting. The use of Tocilizumab is still controversial due to the contradictory results of the clinical trials. Although there is probably a higher frequency of thrombotic events in COVID-19, therapeutic anticoagulation is not recommended.